WALKING WITH MALU: IMAGERY AND POETIC EXPERIENCES IN RESEARCH WITH CHILDREN - Oliveira, Andreia Regina de [UNESP]; Marcolino, Suzana [UNESP]; Souza, Fernanda Cristina de (Fundacao Univ Tocantins, 2020)
It is a devir-article, in the sense of not wanting to imitate, bring models and truths or fixed places of departure and arrival: it is an opening to the countless possibilities of being and researching with children. It seems to us a possible way of thinking about childhood and experiences with children seeking to read, listen, look, feel, with eyes, mouths, ears, arms, hands - with the whole body wide open - in constant and incessant search for novelty and enchantment. Through a poetic, aesthetic and imagery composition, we will seek to walk aphoristic paths to think about children, childhood and disability. Reticent, we think and build new knowledge and do about and with childhood and children. With the images produced by Malu, we are invited to enter places, spaces and other times that put us in motion, in coming, in opening, in search of discoveries, curiosities, novelties, much more than certainties.
Keywords: Child; Childhood; Imaging experiences; Disability